MAQASID SHARIA IN TABARRU’ CONTRACT LAWS - Al-Ayyubi, Solahuddin; Herindar, Evania; Perdana, Muhammad Nabhan (Jurnal Al-Dustur, 2023)
A Research related to maqasid sharia in the tabarru’ contract law had to be very seldom. With this research that examines two purposes, including, first, to determine the role of maqasid sharia in Islamic finance. Second, to determine the existence of maqasid sharia in tabarru’ contract laws. By using qualitative approach, the data for this study was obtained from relevant books, journals, and other academic materials and supporting documents. The results of this study show that there are many roles of tabarru’ contract, first, generally tabarru'at contract is reproduced considering that it contains several benefits. Second, tabarru' contract is issued voluntarily without the slightest doubt because this contract is a good deed and generosity. Third, improving the means of organizing tabarru’ contracts according to the wishes of the donors. Fourth that donations should not be used as an excuse to waste other people's money, ranging from the rights of heirs to the debts of people who are in debt. This study will contribute to the literature on maqasid sharia in tabarru’ contract laws and Islamic finance.